DEVELOPMENT OF E-LEARNING MODULES FOR INFORMATION SYSTEMS STUDIES BASED ON BALINESE LOCAL WISDOM - Permana, Agus Aan Jiwa; Jayanta, I Nyoman Laba (Journal of Education Research and Evaluation, 2019)
The learning process in college is not just reading material, doing assignments, collecting assignments, and then completing. If it is examined closely with the material presented it can be tedious and after the learning process does not increase students' knowledge. The most likely thing to do is to improve teaching material in an innovative direction that can improve graduate competency. So based on the 2016 curriculum, a Tourism Information System (TIS) course appears. Students who graduate need to be provided with knowledge about this TIS, especially because in Bali it is a world tourist destination.In realizing this, learning tools are needed to help, so a module is created to help the learning process that integrates SIP with the local culture of Bali to produce more attractive promotions that are accessed in E-learning.